Socio-Economic Analysis of Local Papuan Communities Rejecting Transmigration According to Article 33 Paragraph 3 of the 1945 Constitution - M Yosi Ramadan; Mabruri Andatu; M Jahid Lilhaq; Ahmad Saputra; M Rafi Mudzakky (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The economy of Papua Province in 2023 experienced a growth of 5.22 percent, with the main contribution coming from the mining and quarrying sector which reached 39.64 percent. from the mining and quarrying sector which reached 39.64 percent. sector construction and agriculture, forestry, and fisheries also contributed significantly to the economic structure. to the economic structure. Although inflation in the main cities such as Merauke, Timika, and Jayapura show a downward trend, economic inequality and the need for sector diversification remain a challenge. and the need for sector diversification remain a challenge. Through qualitative approach, this study collected data from the Central Bureau of Statistics of Papua Province (BPS), journals, articles, and other sources. Papua (BPS), journals, articles, and books. review of related literature The Papuan people's rejection of the transmigration policy reflects their efforts to maintain their transmigration policy reflects their efforts to maintain their rights to customary land and natural resources integral to their identity. and natural resources that are integral to their identity. Based on Article 33 Paragraph 3 of the 1945 Constitution, natural resource management must provide direct benefits for the welfare of local communities. for the welfare of local communities. This rejection highlights the importance of community involvement in any development policy to ensure social justice, cultural preservation, and economic sustainability.